Multispectral analysis to estimate the turbidity as an indicator of the quality of water in reservoirs in Chihuahua State, Mexico - Amado-Alvarez, Jesús (2018)
The Basin of Conchos River, located in the State of Chihuahua (Mexico), has suffered a marked deteriorationdue to the development of human activities. The urban population growth, industrialization,and agriculture have significantly degraded water resources of this basin. To examine the quality of itswaters, the reservoirs of Las Vírgenes dam, the Colina lake, and La Boquilla dam have been analyzed, determining the parameters of dissolved oxygen, pH, nitrates, total dissolved solids, turbidity and temperature from water samples. Using these data and the spectral information of Landsat 5 satellite images, 30 linear regression models were evaluated; from these models, turbidity obtained the best match. The regions of spectrum 0.52-0.6 μm and 0.63-0.69 μm, provided by the predictor variable, appeared as the ranges of higher correlation with the values of turbidity. The model used to represent the turbidity spatially distributed shows that La Boquilla dam gets the highest values related to the suspension of sediments provided by ephemeral channels throughout the reservoir.